(untitled) (Bioscience Journal, 2022)
Recent studies have shown that nursing professionals have affected sleep quality, yet no relation between sleep quality and body composition has been established. The present study investigated the relation between body composition and sleep quality in nursing professionals. It was a transversal, quantitative, descriptive, and analytical study. Nursing workers from HC-UFU were randomly selected to participate in this study. Interviews were done with validated questionnaire to evaluate sleep quality of the professionals, and a bioimpedance exam was done with a tetrapolar device. Two hundred forty-three professionals of the nursing team participated in the survey, mostly females (n=205; 84.4%), nursing technicians (53.1%). Average abdominal circumference was 91.97±13.83 cm, body fat was 31.668.24% or 24.0711.50 kg. The body mass index (BMI) was 27.094.63. Most participants evaluated sleep quality as bad (n=99; 40.7%) and “Sleep Latency” between 31 and 60 minutes (n=74; 30.5%) in the dominion “Subjective Sleep Quality”. Correlations were observed between: percentage of body water X Sleep Duration Dominion (r=-0.135; p<0.05); water resistance in the body X Dominion Sleep Efficacy (r=0.149; p<0.05); percentage of body fat X “Disfunction During the Day” (r=0.233; p<0.01); fat mass (kg) and fat percentages X “Sleep disturbance”(r=0.148; r=0.177; r=0.182; p<0.01) respectively; BMI X “Sleep Disturbance”, (r=0.146; p<0.05) as well as percentage of lean mass and body water X “Sleep Disturbance” (r=-0.244; r=0.247; p<0.01). This is the first study comparing sleep quality with body composition data in a nursing team. It became clear that more studies should be done to obtain greater knowledge about the health profile of nursing teams and, therefore, establish better plans and solutions for the group studied.